Menciptakan Sumber Daya Manusia Berkarakter pada Lembaga Pendidikan Non Formal Melalui Analisis Pengembangan dan Pengelolaan di Kota Bekasi - Sri Rejeki; Dwi Budi Srisulistiowati (J-MAS (Jurnal Manajemen dan Sains), 2022)
Non-formal education is one type of education organized by the community. Outside of school activities, this education prioritizes the real conditions that exist in the community, what the community needs under certain conditions, can be used as a reference for the implementation of non-formal education. Moral development can be applied in formal and non-formal education to create intelligent, polite, and dignified human resources who are able to compete with other countries. Character education can create a winning mentality for future generations. Teachers and parents must be able to teach them how to behave properly. One example of Non-Formal education is tutoring or Bimbel at PEC (Practical Education Center) located in Bekasi City which instills students' moral behavior and has a vision to shape the character of students with noble, professional, independent and outstanding character. The purpose of this study is to understand concepts, theories related to moral education and human resources, to find out what are the obstacles in building student character formation, and to find out the attitudes needed to shape students' personalities so that they can become better individuals to improve their character. the quality of human resources with character. The teacher's role in learning is closely related to providing students' learning motivation in delivering subject matter. So that teachers are required to change knowledge to students and create a memorable learning process.